2018
DOI: 10.17219/acem/68845
|View full text |Cite
|
Sign up to set email alerts
|

Telocytes in the female reproductive system: An overview of up-to-date knowledge

Abstract: Telocytes are emerging cell population localized in the stroma of numerous organs, characterized by a distinctive morphology - small cell body with very long, slender prolongations, termed telopodes. Those cells can be found in the whole female reproductive system: in the vagina, uterus, oviducts and ovaries, mammary glands and also in the placenta. In our review, we aim at complete and transparent revision of the current knowledge of telocytes' localization and function, enriched by the analysis of the possib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
21
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(22 citation statements)
references
References 56 publications
1
21
0
Order By: Relevance
“…TCs are identified in a wide variety of organs from diverse species including mammals 8 11 , avian 12 , 13 , reptiles 14 , Amphibians 15 and aquatic species 16 , 17 and parasitic worm 18 . They are located in the trachea and lungs 19 , heart 20 and the blood vessels 21 , kidney, ureter, urinary bladder 22 , tongue 23 , oesophagus, stomach and small and large intestines 24 , liver , pancreas 14 , testis 25 , prostate 26 , efferent ductules 27 ovaries, oviducts, uterus, vagina, mammary glands and placenta 26 , spleen 8 , 28 .…”
Section: Introductionmentioning
confidence: 99%
“…TCs are identified in a wide variety of organs from diverse species including mammals 8 11 , avian 12 , 13 , reptiles 14 , Amphibians 15 and aquatic species 16 , 17 and parasitic worm 18 . They are located in the trachea and lungs 19 , heart 20 and the blood vessels 21 , kidney, ureter, urinary bladder 22 , tongue 23 , oesophagus, stomach and small and large intestines 24 , liver , pancreas 14 , testis 25 , prostate 26 , efferent ductules 27 ovaries, oviducts, uterus, vagina, mammary glands and placenta 26 , spleen 8 , 28 .…”
Section: Introductionmentioning
confidence: 99%
“…TCs have been suggested as a type of connecting cell dependent on its telopodes (Tps) and 3D structures, or through secreted mediators, connectors, or ligand receptor for interactions [20]. TCs are known to be involved in organ injury with the ability to promote proliferation and angiogenesis [21]. Our studies demonstrated the effect of TCs on the proliferation, migration and apoptosis of HACAT cells, HDMECs, and L929 cells in the presence of LPS mainly mediated by improving HaCaTs migration and protecting them from LPS-induced apoptosis and cell death.…”
Section: Discussionmentioning
confidence: 99%
“…In the female reproductive system of human, the function of telocytes has not been fully elucidated yet; however, many researchers point at their role in the regulation of local microenvironment, myogenic contractile mechanism, bioelectrical signaling, immunomodulation, and regulation of blood flow. Additionally, previous research suggests that telocytes might act as sex hormone level sensors and are connected with pregnancy maintenance (Janas, Kucybała, Radoń‐Pokracka, & Huras, ). These data reinforce the idea that the telocytes also actively participate in ovary homeostasis and its remodeling throughout reproductive cycles in fish, promoting angiogenesis when necessary and the communication between the stromal and germinal compartments.…”
Section: Discussionmentioning
confidence: 99%